Development of Learning Modelsfor Paddy-Rice Farmers in Under-DevelopedAreain Indonesiathrough Strengthening Capacity and Independence - Amiruddin Saleh, Aida Vitayala S. Hubeis, Budi Sawitri, Siti Amanah (International Journal of Advanced Science and Technology, 2020)
Small-holder family farmers face the issues of poverty and the challenges to fulfill food security. In this case, extension education plays a strategic role to strengthen capacity for the farmers in managing the farm (paddy-rice farm). A survey to paddy-rice farmers in Bondowoso and Belu was conducted to 400 samples from July to September 2019. Multivariate Structural Equation Model (SEM) analysis was used to estimate the precise model for strengthening the farmer’s independence through their capacity. The results showed that the farmer capacity was significantly influenced by the farmer characteristics, food consumption and extension support patterns. The farmer’s independence was directly affected by extension support and local economic institutional support; and was indirectly affected by the farmer’s characteristics, food consumption patterns and extension support through the farmer capacities. Learning model development should be more focused to meet the farmer’s needs, especially the increased production and productivity of rice farming through extension services. The service provided by extension agency is one of the farmers learning resources to obtain information and innovation through the learning process. "BUDDIE" is a model developed and recommended to address the learning problems of paddy-rice farmers in disadvantaged areas as an effort to improve extension services.